ANALISIS PENGELOLAAN PENGETAHUAN DENGAN ASIAN PRODUCTIVITY ORGANIZATION - ASSESSMENT TOOLS PADA PERUSAHAAN PERKEBUNAN INDONESIA - Golfidi Djajasoedarma, Muhammad; Sukmawati, Anggraini; Anggraeni, Elisa (BACA: Jurnal Dokumentasi dan Informasi, 2020)
Various changes that occur in the current business environment requires an organization/company to survive and adapt to various changes that occur in the business environment. So companies can survive in the business environment, they must innovate products, expand markets, improve service quality, improve production processes, improve organizational systems, and make cost savings. A company needs to view knowledge as a valuable and strategic resource. With good knowledge management, organizational resources are not easily imitated by business competitors. Knowledge management in this study uses the APO Assessment Tools framework to assess the maturity level of knowledge management of plantation companies. APO Assessment Tools have 7 categories, namely leadership, processes, people, technology, knowledge processes, learning and innovation, and the results of knowledge management. The results showed that knowledge management in plantation companies in Indonesia was approaching maturity.